The Secret Solution : How One Principal Discovered the Path to Success - Whitaker, Todd, 1959- ; Miller, Sam, 1952- and Donlan, Ryan , 1967- (Lanham, Maryland Rowman & Littlefield Education, 2014)
The secret of effective leadership can elude even the best principals. In The Secret Solution, How One Principal Discovered the Path to Success, a principal travels a journey through four distinct leadership styles as he works to transform a school
Keywords: School management and organization -- School principals -- Educational change